South Africa has joined a global initiative for Family Medicine advocacy - Klaus von Pressentin; Kyle Hoedebecke; Luís Pinho-Costa (South African Family Practice)
The international #1WordforFamilyMedicine initiative serves to explore the identity of family physicians and allows the international Family Medicine community to collaborate on advocating the discipline. South African family physicians provided 42 responses via a social media and online survey. Two “word cloud” images were created based on two icons recognised as being truly South African around the world – the national flag and former president Nelson Mandela. The #1WorldforFamilyMedicine initiative was promoted by the World Organization of Family Doctors across the globe to help celebrate World Family Doctor Day on 19 May 2015. To date, over 70 images have been created in 50 different countries on six continents. The images represent family physicians’ love for their profession and the community they serve. It is hoped that this initiative will help to inspire current and future Family Medicine and primary care providers.